EFEKTIVITAS NANO-HYDROXYAPATITE SEBAGAI UPAYA KURATIF FRACTURE OSTEOPOROSIS MELALUI MEKANISME OSTEOINDUKTIF BONE HEALING (SCAFFOLD): TINJAUAN SISTEMATIS: Tinjauan Sistematis - Febriani, Reka; Reindah, Jessika Janet; Aprilia, Nur Ananta (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Abstract: This study assesses the effectiveness of Nano-Hydroxyapatite (nHAp) in treating fractures related to osteoporosis using experimental animal models based on existing research. The focus is on improving the Quality of Life (QoL) through bone healing mechanisms. Methods: A systematic review employing experimental methods was conducted to induce fractures in animal models with osteoporosis and then treat them with nHAp. Objective: This study aims to evaluate nHAp by measuring clinical and radiological parameters, as well as the histological assessment of the bone healing process. Results: The study found that the use of nHAp significantly improved the bone healing process in animal models. Clinical evaluation demonstrated a notable increase in bone strength due to the impact of immunomodulators. Radiological analysis indicated improved bone regeneration in the nHAp-treated group compared to the control group. At the histological level, there was an increase in the proliferation of osteoblast cells, mineral deposits in the fracture area, and improved flexibility with the scaffold. Conclusion: This study concludes that Nano-Hydroxyapatite (nHAp) is effective as a treatment for osteoporosis-related fractures due to its osteoinductive mechanism. The use of nHAp can accelerate the bone healing process by enhancing the quality of the formed bone, which has the potential to contribute to an improved quality of life for individuals with osteoporosis.